Enhancing University Income Generation Alternative Revenue Resources for the University a Case Study in Universiti Sains Islam Malaysia (USIM) - Hammad Farhi Mohd Saudi (Center for Communication Technology and Human Development (UniMAP), 2024)
The University Transformation Programme was announced by the Ministry of Education Malaysia (MOE), through the launching of the Malaysia Education Blueprint (MEB) 2015-2025 (Higher Education). The MEB (HE) outlines 10 Shifts. Out of the ten shifts, Shift#5: Financial Sustainability aims to ensure long term financial sustainability of the higher education system. To achieve this goal, a relevant governance structures is needed. Simultaneously, the income generation activities at the universities is expected to be strengthened, while staying focused on their core education mission. As public universities are given greater autonomy, universities can create any strategies to generate income successfully. Thus, this case study will attempt to address the needs for USIM to seek for potential alternative income generation. Besides, relying on tuition fees imposed to the students which is the main contributor to USIM in generating income, there is another possible income generating channel that could contribute to USIM’s strategy for getting revenue. The possibility of offering Premium Student Accommodation targeting International Students as tenants will be the research topic of this case study. This case study is of great significance as it will identify an alternative source of income that can be benefited by the university. This case study will explore the requirement and expectation of its international student in terms of accommodation. It will assist the University’s Management to make use of the current asset and turn them into a potential source of income.